Arachne bewohnt den Westen / Text: Martin Walsers körperliche, räumliche und textuelle Interkulturalität - Palimariu, Ana Maria (Amaltea. Revista de Mitocrítica, 2010)
In the novel Ein fliehendes Pferd as also in his next novel Brandung the narrator shows that he is leading a dialogue with Goethe and that „he has seen through the illusion of its own originality“ 240). The other illusion nevertheless, the illusion to be able to distinguish between a narrator and a main character, turns out for the reader to be futile. Moreover: by means of a complicity between the narrator and the main character and by means of their subversiveunidirectional gaze at the opposite character, this character would become not only predatory-animal and godly features, but also space-appropriating forms, which would strongly remind us of the myth of Arachne, who was transformed into a spider. Martin Walser can fundamentaly re-interpret the myth of Arachne, by means of endowing the american womenhood not only with the conventional spidery attributes (as a chimera), but also additionally with godly attributes (as a demi-godess), which would rather recall the figure of Arachne’s competitor Athene.